A comparative study of spanning tree and gossip protocols for aggregation. (28th May 2015) - Nyers, Lehel; Jelasity, Márk
Summary: Distributed aggregation queries like average and sum can be implemented in different paradigms like gossip and hierarchical approaches. In the literature, these two paradigms are routinely associated with stereotypes such as 'trees are fragile and complicated' and 'gossip is slow and expensive'. However, a closer look reveals that these statements are not backed up by systematic studies. A fair and informative comparison is clearly needed. However, this is a hard task because the performance of protocols from the two paradigms depends on different subtleties of the environment and the implementation of the protocols. We tackle this problem by carefully designing the comparison study. We use state‐of‐the‐art algorithms and propose the problem of monitoring the network size in the presence of churn as the ideal problem for comparing very different paradigms for global aggregation. Our simulation study helps us identify the most important factors that differentiate between gossip and spanning tree aggregation: the time needed to compute a truly global output, the properties of the underlying topology, and sensitivity to dynamism. We demonstrate the effect of these factors in different practical topologies and scenarios. Our results help us to choose the right protocol in the light of the topology and dynamism patterns. Copyright © 2015 John Wiley & Sons, Ltd.